PENERAPAN METODE DEMONSTRASI DALAM MENINGKATKAN PEMAHAMAN PELAJARAN - Khoirum Anisah; Hilyah Ashoumi (JoEMS (Journal of Education and Management Studies), 2020)
The teaching and learning process is the core of the overall education process, the teacher as the main role holder. One part of the learning planning component is the method. The method is a method used to achieve the stated goals. Demonstration method is a teaching method that uses demonstration to clarify an understanding to show students how to do something. In the learning process there will certainly be obstacles and of course it will also lead to solutions. the application of demonstration methods in jurisprudence learning in class 1A Special Program Madrasah Mu'allimin Mu'allimat Bahrul Ulum Tambakberas Jombang, the obstacles that exist in applying the method of demonstration of fiqh subjects in class 1A Special Program, the solution will be done to overcome problems in the application of Jombang a demonstration method in improving the understanding of fiqh subjects in 1A Special Program students. This type of research is a descriptive study with a case study method, where the data obtained is the result of interviews and questionnaires in class 1A students. This case study is a method for collecting and analyzing data regarding a case. Based on the results of research on problems in applying the demonstration method, it can be concluded as follows: Lack of foundation for students because it still transcends the transition period and there are still many students who are still unable to understand the subject of jurisprudence based on the yellow book accompanied by the necessity to master Arabic script pegon, so it takes time to increase understanding further. Not all chapters in the book of jurisprudence can be packaged by using the demonstration method. Solutions are carried out to overcome the problems in applying the demonstration method in Class 1a Madrasah Special Program Students Mu'allimin Mu'allimat Bahrul Ulum Tambakberas Jombang, that is related to the initial foundation of a student, that is, being able to read and write using Arabic pegon writing, therefore teachers are expected to be more active in providing guidance in the form of direction and motivation, so that the method is easier to understand along with increasing yes writing the writing.